Comparison of Indonesian Herbal Drinks Empon-empon and Wedang Pokak for Vitamin C Content and Antioxidant Activity - Nur Hasanah; Sheila Meitania Utami; Intan Tsamrotul Fu’adah; Dwina Ramadhani Pomalingo; Beny Maulana Satria; Pugoh Santoso; Silvester Maximus Tulandi; Ayu Indayanti Ismail (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Empon-Empon and Wedang Pokak are traditional Indonesian herbal drinks prepared from various spices through a simple production process. Empon-Empon consists of red ginger, turmeric, nutmeg, aromatic ginger, bay leaves, lemongrass, galangal, cinnamon, and cloves. At the same time, Wedang Pokak contains red ginger, cloves, lemongrass, cinnamon, cardamom, pandan leaves, and star anise. Both drinks are widely recognized as sources of antioxidants and vitamin C, and are believed to strengthen the immune system. This study aimed to determine the vitamin C content and antioxidant activity of Empon-Empon and Wedang Pokak. Vitamin C analysis was carried out using UV-Vis spectrophotometry, which showed a maximum wavelength at 245 nm with a linear regression equation y = 0.0434x – 0.0967 (R² = 0.9942). The vitamin C content was 23.33 µg/mL (0.233%) in Empon-Empon and 20.28 µg/mL (0.202%) in Wedang Pokak. Antioxidant activity was determined using the DPPH method, yielding inhibition percentages of 21.28% (20 µg/mL), 40.16% (40 µg/mL), 46.48% (60 µg/mL), and 59.67% (80 µg/mL) for Wedang Pokak, with an IC₅₀ value of 63.33 µg/mL. This activity was lower than Empon-Empon (IC₅₀ 40.53 µg/mL) and pure vitamin C (IC₅₀ 3.77 µg/mL). In conclusion, Empon-Empon exhibited higher vitamin C content and stronger antioxidant activity than Wedang Pokak, highlighting its potential as a functional drink to support health.